4D BIM 기반의 건설프로젝트 작업공간 계획 프로세스 - 최병주; 이현수; 박문서; 김현수; 황성주; Choi, Byungjoo; Lee, Hyun-Soo; Park, Moonseo; Kim, Hyunsoo; Hwang, Sungjoo (한국건설관리학회 논문집, 14(5), 2013)
Each participant in building construction project requires their own workspace to execute their activities. In this environment, inappropriate workspace planning in construction site causes workspace conflicts which result in a loss of productivity, safety hazard and poor-quality issues. Therefore, workspace should be regarded as one of the most important resources and constraints have to be managed at construction site. However, current construction planning techniques such as Gantt chart, network diagram and critical path method have proven to be insufficient to workspace planning. This paper contains formalized process for workspace planning in 4D BIM environment to prevent workspace related problems in construction project. The proposed process in this paper represents workspace occupation status for each activity and suitable solutions for identified workspace conflicts by integrating workspace attributes and activity execution plan. Based on the result of this study, project manager will be able to prevent probable workspace conflicts and negative effect on project performance by devising appropriate workspace plan during preconstruction phase. 건설프로젝트에서는 다양한 참여자들이 제한된 공간에서 각자의 작업공간을 차지하며 작업을 수행한다. 작업공간에 대한 부적절한 계획은 건설프로젝트의 생산성 감소, 작업 위험 증가 및 품질 저하 등의 문제로 이어지기 때문에 작업공간은 건설프로젝트에서 고려하여야 할 중요한 요소 중 하나이다. 그러나 기존의 건설프로젝트 공사 계획 수립을 위한 방법들은 건설프로젝트에서의 작업공간을 고려하지 못하는 한계가 있었다. 따라서 본 연구에서는 체계적이지 못한 작업공간 계획으로 인하여 발생하는 작업공간 간섭 문제를 예방하기 위하여 4D BIM(Building Information Model) 기반의 작업공간 계획 프로세스를 제안한다. 제안된 프로세스는 각 작업공간의 특성과 공사수행계획을 반영하여 각 액티비티의 작업공간 점유상태를 표현하고 이를 바탕으로 발생 가능한 작업공간 간섭을 발견한다. 또한 각 액티비티와 작업공간의 특성 그리고 공사수행계획 등을 고려하여 발견된 작업공간 간섭에 대한 해결책을 도출한다. 본 연구의 결과를 바탕으로, 프로젝트 관리자는 본 공사 수행 이전에 공사에 필요한 작업공간을 미리 계획함으로써 서로 다른 액티비티 작업공간 사이의 간섭을 예방하고 건설프로젝트에서의 불필요한 손실을 예방할 수 있다.